SLA-ORIENTED SEMI-AUTOMATIC MANAGEMENT OF DATA STORAGE AND APPLICATIONS IN DISTRIBUTED ENVIRONMENTS - Król, Dariusz; Funika, Włodzimierz; Słota, Renata; Kitowski, Jacek (Computer Science, 2013)
In this paper we describe a semi-automatic programming framework for supporting userswith managing the deployment of distributed applications along with storing large amountsof data in order to maintain Quality of Service in highly dynamic and distributed environments,e.g., Grid. The Polish national PL-GRID project aims to provide Polish science withboth hardware and software infrastructures which will allow scientists to perform complexsimulations and in-silico experiments on a scale greater than ever before. We highlight theissues and challenges related to data storage strategies that arise at the analysis stage ofuser requirements coming from different areas of science. Next we present a solution to thediscussed issues along with a description of sample usage scenarios. At the end we provideremarks on the current status of the implementation work and some results from the testsperformed.